Estudo comparativo das formas uai, uê e ué em Itaúna/MG e Piranga/MG - Débora Priscila Simião (2016)
This research has as main goal to make a comparative analysis, on the Variationist Sociolinguistics (LABOV, 1972) field, between the forms UAI, UÉ and UÊ in two cities of Minas Gerais, Itaúna and Piranga. According to the division proposed by Nascentes (1953) the first of those two cities is situated in the mineiro speaking area on the limits of the paulista or sulista speaking area while the second one is located in the fluminense speaking area. Thus, we will make an analysis of the forms mentioned considering them variants on specific contexts. Two different variables were analyzed in this study: UAI1 and UAI2. This division was made based on the different contexts assumed by the variable, object of this research. The data, collected by the research group Varfon-Minas, were submitted to a process of acoustic analysis; we used also the chi-square test. Our analysis aims to observe mainly the influence of social factors of gender and age group, assumed here as independent variables, in the use that the speakers make of these forms. Our initial hypothesis was that the use of the analyzed variables occurs differently in the two speaking communities researched. It is also a goal of this dissertation to present a proposal to the possible source of the form UAI, drawing a route to the development of those variants. We conclude that there was a process of lexicalization related to the two studied variables.